Mechanical Behavior of Polyurethane Stabilized Fouled Ballast (PSFB) - Dolcek, Tolga (My University, 2014)
The United State Federal Railway Administration (FRA, 2010) estimates that the demand for rail freight transportation (tonnage) will increase 88% by 2035. North American railroads spend about $3.4 billion every year on track substructure maintenance and renewal due to track-component degradation (Li et al. 2004). These increases in traffic density and weight will cause more deformation and, consequently, more maintenance of the ballast layer. An alternative method in order to decrease maintenance cost is desirable. One such method is injection of polyurethane resin at critical locations in the ballast. This method is effective on clean ballast as a preventive measure (Keene at al. 2012). This study is aimed at evaluating its effectiveness in remediating fouled ballast through polyurethane injection clean ballast was mixed with various types of fouling at different amounts, water contents, and sealed in rectangular (76 mm x 76 mm x 290 mm) and cylindrical (254 mm x 508 mm) molds. The polyurethane was injected into the molds and the specimens were cure for 24 hours. Testing protocol was developed to quantify plastic deformation, flexural strength, and unconfined compressive strength of the fouling ballast stabilized by polyurethane. Average flexural strength of PSB (938 kPa) is about 35% greater than the average flexural strength of PSFB (611 kPa). The average UCS strength of the PSB specimens (3200 kPa) is greater than that of the PSFB specimens (2713 kPa). However, PSFB has a greater strength (about 74%) than unstabilized clean ballast. The PSFB cylindrical specimen with different FI and WC under cyclic loading with deviator stress, ?d of 350 kPa, the plastic strains vary between 0.9% - 1.02%, which are under the FRA limit for maintenance (2.5% - 3%) (Hesse, 2013, Keene et al. 2012). The results show that the injection of polyurethane into fouled ballast significantly reduces plastic strain and increases strength. Increasing amounts of fouling material and water content reduces strength and increases plastic strain. Results of this study are then compared with a previous study on clean ballast injected with polyurethane. The use of polyurethane injection into the ballast has the potential to be a fast and cost effective solution for maintenance of the railway systems.